Reading museums - Tzortzi, Kali (Qualitative and Quantitative Methods in Libraries; Vol 4 No 2 (2015): June 2015 Issue, 2017)
The paper takes as starting point the idea that museums, like libraries, can be thought of as „maps of knowledge‟, which order things in space according to some abstract scheme and where movement acquires a conceptual dimension. Through the study of three museums, it proposes an analytic methodology that helps us to clarify how the arrangement of objects can both reflect knowledge, reinforcing current understanding, and generate a sense of knowledge that is non-discursive, potentially reordering understanding. Borrowing key concepts from the mathematical theory of communication, the paper shows how predictability and unexpectedness are created through space and display design, by balancing structure and randomness, and how they affect the exploration of the museum and the reading of the display by visitors. It ends by raising the question if this contrast in museums can be theoretically related to the debates about browsing exploration in libraries and the concept of serendipity.